Lung cancer correlates in Lebanese adults: A pilot case-control study - Joseph Aoun; Nadine Saleh; Mirna Waked; Joseph Salamé; Pascale Salameh (Springer, 2019)
Background: Lung cancer is one of the most prevalent types of cancers. However, there are no epidemiological studies concerning lung cancer and its risk factors in Lebanon. This study was carried out to determine the association between lung cancer and its most common risk factors in a sample of the Lebanese population. Methods: A hospital-based case-control study was conducted. Patients were recruited in a tertiary health care center. A questionnaire in Arabic was designed to assess the possible risk factors for lung cancer. Results: For females, cigarette smoking (ORa = 9.76) and using fuel for heating (ORa = 9.12) were found to be the main risk factors for lung cancer; for males, cigarette smoking (ORa = 156.98), living near an electricity generator (ORa = 13.26), consuming low quantities of fruits and vegetables (ORa = 10.54) and a family history of cancer (ORa = 8.75) were associated with lung cancer. Waterpipe smoking was significantly correlated with lung cancer in the bivariate analysis. Conclusion: In this pilot study, it was found that in addition to smoking, outdoor and indoor pollution factors were potential risk factors of lung cancer. Additional studies would be necessary to confirm these findings.